Involvement of brain structures in childhood epilepsy with centrotemporal spikes. Issue 1 (20th April 2022) - Ito, Yuji; Maki, Yuki; Okai, Yu; Kidokoro, Hiroyuki; Bagarinao, Epifanio; Takeuchi, Tomoya; Ohno, Atsuko; Nakata, Tomohiko; Ishihara, Naoko; Okumura, Akihisa; Yamamoto, Hiroyuki; Maesawa, Satoshi; et al.
Abstract: Background: We aimed to investigate electroencephalography (EEG)‐functional magnetic resonance imaging (fMRI) findings to elucidate the interictal epileptiform discharge (IED)‐related functional alterations in deep brain structures and the neocortex in childhood epilepsy with centrotemporal spikes (CECTS). Methods: Ten children with CECTS (median age 8.2 years), referred to our hospital within a year of onset, were eligible for inclusion. They underwent EEG‐fMRI recording during sleep. Llongitudinal evaluations, including medical examinations, intelligence tests, and questionnaires about developmental disabilities, were performed. The initial evaluation was performed at the same time as the EEG‐fMRI, and the second evaluation was performed over 2 years after the initial evaluation. Results: Three children were unable to maintain sleep during the EEG‐fMRI recording, and the remaining seven children were eligible for further assessment. All patients showed unilateral‐dominant centrotemporal spikes during scans. One patient had only positive hemodynamic responses, while the others had both positive and negative hemodynamic responses. All patients showed IED‐related hemodynamic responses in the bilateral neocortex. For deep brain structures, IED‐related hemodynamic responses were observed in the cingulate gyrus ( n = 4), basal ganglia ( n = 3), thalamus ( n = 2), and default mode network ( n = 1). Seizure frequencies at the second evaluation were infrequent or absent, and the longitudinal results of intelligence tests and questionnaires were within normal ranges. Conclusions: We demonstrated that IEDs affect broad brain areas, including deep brain structures such as the cingulate gyrus, basal ganglia, and thalamus. Deep brain structures may play an important role in the pathophysiology of CECTS.